Association Between 25(OH)Vitamin D, HbA1c and Albuminuria in Diabetes Mellitus: Data From a Population-Based Study (VIDAMAZON) - Felício, João Soares; de Rider Britto, Hana Andrade; Cortez, Pedro Celeira; de Souza Resende, Fabrício; de Lemos, Manuela Nascimento; de Moraes, Lorena Vilhena; de Aquino, Vitória Teixeira; de Souza Parente, Fernanda; de Queiroz, Natércia Neves Marques; Abrahão Neto, João Felício; de Alcântara, Angélica Leite; da Silva, Wanderson Maia; et al. (Frontiers in Endocrinology, 2021)
Background: The effect of glycemic control on diabetic kidney disease (DKD) is well known. Recent evidence has suggested that Vitamin D (VD) may have a nephroprotective effect in diabetes, but the relationship between VD, glycemic control, and albuminuria has yet to be clarified. Objective: Evaluate the relationship between 25-hydroxy-vitamin D [25(OH)D], HbA1c, and albuminuria in Diabetes Mellitus (DM). Patients and Methods: Cross-sectional study with 1576 individuals with DM who had 25(OH)D, HbA1c, and albuminuria levels measured. Patients with abnormal creatinine levels were excluded, in order to avoid interference on VD levels by impaired kidney function. Results: Patients with HbA1c ≥7% had lower 25(OH)D when compared to patients with HbA1c <7% (29.7 ± 10.2 vs 28.1 ± 9.9 ng/ml, p = 0.003) and 25(OH)D levels seems to predict 1.5% of HbA1c behavior. The 25(OH)D concentrations in patients with normoalbuminuria were higher than the levels observed in those with micro or macroalbuminuria (29.8 ± 9.0 vs 26.8 ± 8.6 and 25.1 ± 7.6, respectively, p = 0.001), patients who had 25(OH)D <20 ng/ml and 25(OH)D <30 ng/ml were at a higher risk of presenting albuminuria [OR = 2.8 (95% CI = 1.6 – 4.9), p<0.001, and OR = 2.1 (95% CI = 1.3 - 4.6), p<0.001, respectively]. In our regression model, albuminuria was influenced by HbA1c (r² = 0.076, p<0.00001) and 25(OH)D (r² = 0.018, p = 0.002) independently. Conclusion: Our study found an association between vitamin D levels, HbA1c and DKD. Additionally, our data suggest that the association between urinary albumin excretion and vitamin D levels is independent of glycemic control in patients with diabetes. Even though our patients presented normal creatinine levels, it is necessary further prospective studies to confirm if this association precedes or not the loss of renal function.